ANALISIS SEKTOR KEUANGAN TERHADAP PERTUMBUHAN EKONOMI REGIONAL DI WILAYAH JAWA: PENDEKATAN MODEL LEVINE - Utami Baroroh (ETIKONOMI, 2012)
The objectives of this study are to analyze the influence of financial development to economic regional growth on Jawa region, using panel of province-level data on Jawa region for the period 2005-2010. The analysis method that used on this paper is panel data regression. The empirical results shown that financial asset and financial credit had a positive influence to economic regional growth on Jawa region, meanwhile third party fund had negative influence to economic regional growth on Jawa region.  The other result shown that individual effect from fixed effect model showed that DKI Jakarta, Banten and East Jawa have potential as the centre of economic growthDOI: 10.15408/etk.v11i2.1892